2020
DOI: 10.1111/ijfs.14910
|View full text |Cite
|
Sign up to set email alerts
|

Mango (Mangiferaindica L.) leaf extracts as ingredient for the formulation of functional beverages with biological activity

Abstract: The biological activity of mango leaf extracts from different mango varieties was evaluated in terms of total phenolic content, flavonoids, antioxidant activity and inhibition of a-amylase and a-glucosidase enzymes. Leaf extract-based beverages were formulated and evaluated for some physicochemical, microbiological and sensory properties. Results indicated that the extract from 'Tommy Atkins' mango leaves had the highest total phenols content (137.08 mg of GAE g À1 ) and antioxidant activity (DDPH = 38.26 mg T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…For this study, mango leaves from the Ataulfo variety were selected as in previous studies, this variety showed the best antioxidant and inhibitory activity on α‐amylase and α‐glucosidase enzymes (Medina‐Saavedra et al ., 2021). Mango leaves were collected from the National Institute for Forestry, Agriculture and Livestock Research (Instituto Nacional de Investigaciones Forestales, Agrícolas y Pecuarias: INIFAP), located in Cotaxtla, Veracruz, Mexico during July 2020.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For this study, mango leaves from the Ataulfo variety were selected as in previous studies, this variety showed the best antioxidant and inhibitory activity on α‐amylase and α‐glucosidase enzymes (Medina‐Saavedra et al ., 2021). Mango leaves were collected from the National Institute for Forestry, Agriculture and Livestock Research (Instituto Nacional de Investigaciones Forestales, Agrícolas y Pecuarias: INIFAP), located in Cotaxtla, Veracruz, Mexico during July 2020.…”
Section: Methodsmentioning
confidence: 99%
“…TPC was determined using the Folin–Ciocalteu colorimetric method described by Medina‐Saavedra et al . (2021). TPC was calculated using a standard curve of aqueous gallic acid solutions (0–10 mg gallic acid mL −1 ) and expressed as mg gallic acid equivalents (GAE) g −1 of sample.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the residues and the by‐products (e.g., bark, husks, stems, seeds, and leaves) from plants of fruits and vegetables are potential and alternative source for the study of various biological activities such as antidiabetic, antioxidant, antibacterial, among others. Roots and Mangifera indica L. leaves have been used since ancestral times as traditional medicine (Díaz‐Torres et al, 2017; Medina‐Saavedra et al, 2021).…”
Section: Introductionmentioning
confidence: 99%